Evaluation of Variability in Proximate Compositions among Accessions of Sword bean (Canavalia gladiata Jacq. DC) and Jack bean (Canavalia ensiformis L. DC) - Oyeyemi Adigun DADA; Benjamin FALOYE; Juliet Dominique DUMET (Notulae Scientia Biologicae, 2013)
Exploitation of available germplasms particularly in the developing countries is still limited despite the availability of rich gene pools. Canavalia species are underutilized legumes of wide importance for humans and livestock feed. Field and laboratory studies were carried out on evaluation of variability in proximate compositions within and between fifteen genotypes of Canivalia species collected from Genetic Resources Centre, International Institute of Tropical Agriculture (IITA), Ibadan. The study was a randomized complete block design replicated three thrice. Harvested mature seeds were analysed for proximate composition. The results revealed that moisture content ranged from 26.97 to 30.05, crude protein 15.45-21.85%, lipid 7.05-29.70%, ash 10.18-17.43%, sugar 0.75-1.37%, starch 7.40-0.26% and energy levels 1016.56-1825.82 kJ 100 g-1 DM. Significant (p<0.05) variability was observed in sugar, lipid and energy contents among the accessions based on analysis of variance (ANOVA). The first principal component analysis (PCA) had the highest contribution of 31.4% to the total variation. Based on proximate composition, the 15 accessions clustered into six main groups. Lipid varied widely and significantly (p<0.05) correlated to energy. Aggregation of accessions within the same species into a cluster revealed high similarity within a biological and taxonomic unit. The similarities among these 15 accessions could allow for inter specific hybridization.